Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Minat Investasi Milenial dengan Sikap Keuangan - T, Tri Adelia; Jasman, Jumawan; Syamsuddin, Sofyan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of financial literacy and lifestyle on millennials' investment interest, with financial attitude as a mediating variable. This research employs a quantitative method, collecting primary data through an online questionnaire from 200 millennial respondents in North Luwu Regency. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that financial literacy and lifestyle significantly influence investment interest. Additionally, financial literacy and lifestyle also affect financial attitude. Financial attitude is proven to mediate the relationship between financial literacy and investment interest, as well as between lifestyle and investment interest. The implications of this study highlight the importance of enhancing financial education for millennials to enable them to make wiser investment decisions. Furthermore, policies that promote a financially healthy lifestyle can help raise awareness and increase investment participation among millennials.
Keywords: Financial Literacy; Lifestyle; Financial Attitude; Investment Interest